Assessment of CMIP6 models' performances and projection of precipitation based on SSP scenarios over the MENAP region. Issue 10 (19th October 2022) - Mesgari, Ebrahim; Hosseini, Seyed Asaad; Hemmesy, Maliheh Sadat; Houshyar, Mahmoud; Partoo, Leila Golzari
Abstract: Precipitation is the main component of the hydrological cycle. It has a significant effect on the ecosystem especially, irrigation and drainage system design and management, crop production, and flood and drought management. In this study, 11 global circulation models (GCMs) from Coupled Model Intercomparison Project phase 6 (CMIP6) were investigated under three shared socioeconomic pathway (SSP) scenarios for precipitation simulation and projection in the future period (2021–2050). Then, the results were compared with the base period (1985–2014). The research was conducted in the MENAP region. The evaluation of GCMs' performances by the Taylor diagram, R 2, MSE, MAE, and RMSE indices showed that among the 11 models, the MPI-ESM1-2-HR model with an average R 2 and RMSE of 0.6 and 18.9, respectively, was more accurate than other models in precipitation simulation in the entire region. The projection of precipitation indicated that the precipitation will mainly decrease except in areas such as the Black Sea, Mediterranean, and Red Sea coastal areas as well as mountainous and higher altitude regions in the eastern part of the study area. In addition, highest decrease rates will happen in the Middle East countries, Afghanistan, Morocco, Algeria, and Sudan. Based on different scenarios in the MENAP region, precipitation will vary between −77.3 and + 51.1 mm compared to the base period. Moreover, the lowest and highest precipitation changes were estimated based on SSP1-2.6 and SSP5-8.5 scenarios. According to the various scenarios, the amount of precipitation in the future period will decrease compared to the historical period in most parts of the areas under study. HIGHLIGHTS: Analysis of the 11 global circulation models (GCMs) of the Coupled Model Intercomparison Project phase 6 (CMIP6). Using the three shared socioeconomic pathway (SSP) scenarios. Study of 220 meteorological stations in the MENAP (Middle East, North Africa, Afghanistan, and Pakistan) region. Assessment of CMIP6 model's performance by the Taylor diagram, R 2, MSE, RMSE, and MAE. Using the grid data of ERA5 and GCMs.